Influence of Trichoderma harzianum inoculation and pruning on the growth and yield of Capsicum chinense Jacq. (Agroindustrial Science, 2024)
The production of Capsicum chinense Jacq. is an economically important activity in Mexico. Trichoderma harzianum inoculation and pruning to three and four stems on plant growth, fruit quality, and yield of C. chinense was evaluated. A factorial experimental design A (inoculation and non-inoculation of T. harzianum) × B (pruning to three and four stems) was employed, establishing four treatments. The plant height, stem diameter, fruit quality (fruit- weight, length, and width), and yield (fruits plant-1, g plant-1, and t ha-1) were measured. Inoculation of T. harzianum increased plant height (from 4.3 to 7.9%), without favoring yield. Pruning to three stems increased the plant height (from 7.7 to 14.5%), fruit weight (7.7%), and yield [fruits plant-1 (25.8%), g plant-1 (26.3%), and t ha-1 (26.3%)]. Inoculated plants with T. harzianum and pruned to three stems showed the best yield (15.38 t ha-1) compared to plants inoculated with T. harzianum and pruned to four stems (10.71 t ha-1). T. harzianum favored the vegetative growth, while pruning improved fruit weight and the yield of C. chinense.
Keywords: Biofertilizer; biological agriculture; habanero pepper; fruit quality; stems